High-Performance Liquid Chromatography as a Novel Method for the Determination of α-Defensins in Synovial Fluid for Diagnosis of Orthopedic Infections - Melicherčík, Pavel; Klapková, Eva; Kotaška, Karel; Jahoda, David; Landor, Ivan; Čeřovský, Václav (Diagnostics (Basel, Switzerland), 2020)
The α-defensins (AD) present in synovial fluid have been regarded as constituting the most accurate periprosthetic joint infection (PJI) biomarker. The methods most commonly used for estimating AD as a biomarker are the qualitative Synovasure® PJI tests, based on the technique of lateral flow, and quantitative enzyme-linked immunosorbent assay (ELISA). Here, we propose a novel test based on detecting α-defensins in synovial fluid by high-performance liquid chromatography (HPLC). Synovial fluid was collected from 157 patients diagnosed with PJI, infectious arthritis (IA), arthrosis, reactive arthritis, and rheumatoid arthritis. AD concentrations in the fluid were determined by HPLC, and these same samples were used for additional diagnostic analyses. The results were statistically processed to calculate cutoff concentrations for PJI and IA. HPLC testing showed a sensitivity of 94% and a specificity of 92% for diagnosis of PJI, and a sensitivity of 97% and a specificity of 87% for diagnosis of IA. Using HPLC, we detected in synovial fluid a combination of three α-defensins: human neutrophil peptides HNP1, HNP2, and HNP3. All measured AD concentration values shown in this work refer to the sum of these three individual concentrations. Our study shows that the HPLC method meets the conditions for measuring precise concentrations of the sum of AD and can be recommended as part of a diagnostic array for PJI and IA diagnostics. By this method, we have verified that higher levels of AD in synovial fluid can also be seen in rheumatoid illnesses, crystal arthropathies, and reactive arthritis.
Keywords: arthrosis; synovial fluids biomarkers; infectious arthritis; HPLC; periprosthetic joint infections; α-defensins